Pengaruh Customer Satisfaction Terhadap Online Travel Agent – Sebuah Studi Literatur - Nurhadewa, Kresna; Setiawan, Amelia; Djajadikerta, Hamfri (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The phenomenon of purchasing products online is currently increasing. This causes companies to strive to improve the quality of products (goods and services) to face the challenges currently being faced. One of the phenomena of using the internet and media is the increasing search for information about travel agents (online travel agents). Service quality makes customer satisfaction increase. Consumer satisfaction occurs when a product (goods/services) can meet the needs and desires of a consumer. Satisfaction with a product will lead to brand loyalty so that consumers will repurchase a product and will be able to recommend the product to others. In the world of e-commerce, especially in the field of online travel agents (OTA), customer satisfaction is of great concern. This study uses the sample characteristic method to find the relationship between customer satisfaction and online travel agents. This study illustrates that the service quality of online travel agents can increase customer satisfaction. In knowing the level of customer satisfaction, information systems are divided into three approaches, namely information quality, system quality, and service quality.